Older adults exhibit declines in instrumental activities of daily living during a virtual grocery shopping task - Lewis, Morgan McGrath; Waltz, Colin; Scelina, Kathryn; Scelina, Logan; Owen, Kelsey; Hastilow, Karissa; Miller Koop, Mandy; Rosenfeldt, Anson B.; Alberts, Jay L. (Frontiers in Virtual Reality, 2023)
The successful performance of instrumental activities of daily living (IADLs) is critical in maintaining independence for older adults. Traditional IADL questionnaires and performance-based assessments are time consuming, potentially unreliable, and fail to adequately consider the interplay between cognitive and motor performance in completing IADLs. The Cleveland Clinic Virtual Reality Shopping (CC-VRS) application was developed to objectively quantify IADL performance through the characterization of cognitive, motor, and cognitive-motor function. The CC-VRS combines an immersive virtual grocery store with an omnidirectional treadmill to create a scenario in which the user physically navigates through a virtual environment. The primary aim of this project was to determine the known-group validity of the CC-VRS platform to characterize IADL performance in healthy older adults and young adults.Methods: Twenty healthy young (n=10) and older (n=10) adults completed the Basic and Complex CC-VRS scenarios. Position data from VR trackers on the hands, waist, and feet were used to quantify motor performance. Cognitive and dual-task performance were automatically calculated by the application during specific shopping sub-tasks.Results: Older adults exhibited significantly worse performance on multiple cognitive, motor, and dual-task outcomes of the CC-VRS (i.e., average walking speed, number of list activations, and stopping frequency).The CC-VRS successfully discriminates IADL performance between young and healthy older adults. The complex realistic environment of the CC-VRS, combined with simultaneous evaluation of motor and cognitive performance, has the potential to more accurately characterize IADL performance by identifying subtle functional deficits that may precede neurological disease.